The Phenomenon of Unregistered (Sirri) Marriages in Surabaya - Rohman, Holilur; Rifqi, Muhammad Jazil; Rohman, Moh. Faizur; Solikin, Agus; Naf'an, Abdul Wahab (Hikmatuna : Journal for Integrative Islamic Studies, 2024)
Sirri marriage is valid regarding religion but is not registered at the KUA; consequently, its legal force is still problematic. This article answers two problems: first, the phenomenon of sirri marriage in Surabaya; second, maqasid al-syariah analysis of the phenomenon of sirri marriage in Surabaya. This research used descriptive qualitative methodology. The data collection technique used documentation and interview techniques. The results showed that many sirri marriage practices were carried out by the Surabaya community. Many factors cause the choice of sirri marriage, namely the lack of understanding of legal awareness of the mandatory registration of marriage in Indonesia, the factor of pregnancy outside of marriage, and the polygamy factor. Responding to the phenomenon of sirri marriage in Surabaya, the KUA also made various prevention and handling efforts, such as socialization about the importance of marriage registration, the impact of sirri marriage, coaching for perpetrators of sirri marriage, and others. Based on the maqasid al-syariah study, the phenomenon of sirri marriage is not an ideal marriage for Indonesian society because it cannot realize the objectives of sharia.